Analisis positioning produk smartphone dengan pendekatan metode multi dimensional scaling - Ani Ayatun Nikmah; Tetra Hidayati; Yohanes Kuleh (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Ani Ayatun Nikmah, 2016, Smartphone Product Positioning Analysis with Multi Dimensional Scaling Method Approach ( A Case Study of Faculty of Economics and Business, University of Mulawarman ). Guided by Mrs Dr. Tetra Hidayati, SE., M.Si as the First supervisor and Mr. Dr. J. Kuleh, SE.,M.Si as the Second supervisor.The purpose of this study is to analyze the product positioning map Smartphone based on the perception of consumers in the Faculty of Economics and the University Binsis Muawarman Samarinda. The bases used to position the Smartphone products are consumer perceptions of similarity determinant attribute that consists of brand , price , product features , product quality , product design and product guarantee or warranty. Total sample of 60 respondents taken by accidental sampling method. Data were analyzed by analysis of Multi Dimensional Scaling ( MDS ) to determine the reliability and validity as well as product positioning map Smartphone.The results of this study indicate that there are differences between product positioning Smartphone with product attributes that exist in the research and influence the purchasing decisions of consumers to the product being marketed. On the Smartphone product positioning map which resides in one quadrant is the closest competitor of the smartphone while the smartphone is outside quadrant is a competitor away from the Smartphone. While the results of the test of consistency and attitude similarity respondents indicated that there is no consistency of answers / similarities between the attitude of the respondents in assessing the similarity of the attributes Smartphone products.